Analisis Konsumsi Energi Dan Pangsa Pengeluaran Pangan Terhadap Derajat Ketahanan Pangan Rumah Tangga Petani Singkong Di Desa Ngawen, Pati - Maharani, Artita Devi; Avivah Rahmaningtyas; Eska Stefani; Supriyono (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze energy consumption levels, the share of food expenditure, and food security among cassava-farming households in Ngawen Village, Cluwak District, Pati Regency. The research method employed descriptive analysis, utilizing data collection techniques that included interviews, literature studies, observation, and documentation. Sampling through saturated sampling, namely all members of the Sido Rukun farming group who received fertilizer assistance of more than 2,000 kg, resulted in 35 respondents. Data analysis was carried out by calculating household income, household expenditure, energy sufficiency rate, share of food expenditure, and the degree of food security. The results showed that the average energy and protein consumption of cassava farming households did not meet the AKG standards set by the National Food and Nutrition Workshop. As many as 60% of households had an energy consumption level of less than 80% of the required amount, indicating an imbalance in access to food and energy. In addition, the share of food expenditure was relatively high, which has an impact on household food security, being relatively low. keyword: Energy Adequacy; Food Security; Food Expenditure Share; Households